2022
DOI: 10.1007/s11356-021-18192-w
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections among patients referred to hospitals affiliated to Shiraz University of Medical Sciences, southern Iran: a retrospective study in pre- and post-COVID-19 pandemic

Abstract: Intestinal parasitic infections (IPIs) are still a serious public health problem worldwide, particularly in developing countries. The COVID-19 pandemic has affected people’s lifestyles and quality of life. Besides, the prevalence of IPIs is directly associated with environmental sanitation, overcrowding, and personal hygiene. Therefore, the current study aimed to determine the prevalence of IPIs among patients referred to hospitals affiliated to Shiraz University of Medical Sciences by reviewing the available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
5
7
1
Order By: Relevance
“…Findings from the current study are compared with the only two studies published from our region covering a similar study period; one from Saudi Arabia and the other one from Iran [7,8] In both studies, a reduction in the overall prevalence of parasite was noted in the postcovid period, similar to our findings. The data from Saudi Arabia showed an estimated overall prevalence reduction from 26.6% in the pre-covid to 16.5% in the post-covid period, also noting decreases in the types of parasites as follows: B. hominis (6.9% vs. 3.6%), E. coli (5.8% vs. 0.2%), E. histolytica (3.2% vs. 1.8%), and G. lamblia (5.7% vs. 3.2%) [7].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Findings from the current study are compared with the only two studies published from our region covering a similar study period; one from Saudi Arabia and the other one from Iran [7,8] In both studies, a reduction in the overall prevalence of parasite was noted in the postcovid period, similar to our findings. The data from Saudi Arabia showed an estimated overall prevalence reduction from 26.6% in the pre-covid to 16.5% in the post-covid period, also noting decreases in the types of parasites as follows: B. hominis (6.9% vs. 3.6%), E. coli (5.8% vs. 0.2%), E. histolytica (3.2% vs. 1.8%), and G. lamblia (5.7% vs. 3.2%) [7].…”
Section: Discussionsupporting
confidence: 85%
“…The data from Saudi Arabia showed an estimated overall prevalence reduction from 26.6% in the pre-covid to 16.5% in the post-covid period, also noting decreases in the types of parasites as follows: B. hominis (6.9% vs. 3.6%), E. coli (5.8% vs. 0.2%), E. histolytica (3.2% vs. 1.8%), and G. lamblia (5.7% vs. 3.2%) [7]. In Iran, the pre vs post covid prevalence was 5.8% vs 2.8% [8]. Worth noting that in both studies, the prevalence of parasites was lower compared to ours.…”
Section: Discussionmentioning
confidence: 99%
“… 14 However, the overall finding in the current study considerable higher than those previously reported studies in different location of Ethiopia; 6.23% in Bale Robe, 15 9.3% in Mojo, 16 16.6% in Bale Goba, 17 16.65% in Wonago, 18 20.6% in Jimma, 19 and 27.3% in Debre Tabor. 20 Moreover, overall finding of the present study also considerable higher than studies conducted in Ghana (10%), 21 Saudi Arabia (0.5%), 22 Iran (4.4%), 23 Nepal (15.17%), 24 India (7.6%). 25 On the other hand, it was lower than other reports in Ethiopia; 41.3% in Gondar, 26 45.6% in Gondar, 27 47.9% in Hawassa, 28 53.3% in Dembia, 29 and Tanzania 57.1%.…”
Section: Discussioncontrasting
confidence: 60%
“…Intestinal parasitic infections remain a major health challenge in the Global South [ 1 , 2 , 3 ]. The World Health Organization (WHO) reported that about 688 million adolescent girls and women of reproductive age reside in areas with intestinal worm endemicity [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%